(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
The extraterritorial areas envisaged by the Lateran Treaty between the Holy See, Italy, and the Vatican City State ABSTRACT: This paper examines the legal regime of the extraterritorial areas envisaged by the Lateran Treaty stipulated between the Holy See and Italy in 1929. These are buildings and functional areas for the best exercise of the Holy See’s own functions, forming part of the territory of the Italian State but enjoying the immunities proper to diplomatic headquarters. In recent decades, an expansive trend has been observed in Vatican legislation and jurisdiction concerning these areas, which the author highlights by emphasizing the discontinuity with respect to the past. SOMMARIO - 1. Le aree extraterritoriali nel Trattato lateranense. La ratio dell’istituto - 2. Il concetto di extraterritorialità nell’ordinamento internazionale e nel Trattato lateranense - 3. Il complesso sistema di garanzie della Santa Sede nel Trattato lateranense - 4. Gli immobili e le aree soggette a regime di extraterritorialità - 5. Governo civile e legislazione applicabile nelle aree extraterritoriali - 6. L’esercizio della giurisdizione nelle aree extraterritoriali - 7. Giurisdizione penale vaticana e aree extraterritoriali nelle recenti riforme - 8. Giurisdizione ultraterritoriale vaticana e concorrenza di giurisdizioni - 9. Osservazioni conclusive.